Language Model Evolution : GPT and Impact Beyond - Bhattacharjee, Sandeep (Indian Journal of Computer Science, 2023)
Language models are considered a way of machine level of understanding and predicting human languages as a part of human communication relevant to the context. The present research paper tries to understand the growth of such language models popularly known as GPT or Generative Pre-trained Transformer. It tries to understand the meaning, growth, working of model, and some of the applications where GPT is being used. Several applications on business, website development, and conversational applications are now being powered by GPT with tremendous potential for future convergence. Artificial Intelligence and sub-domains. This research paper can be very useful for academicians, researchers, and professionals who handle business and information technology applications.